The Effect of The Characteristics of the Board of Directors and Sharia Supervisory Board on The Distribution of Zakat of Islamic Banks In Indonesia - Hariz, Muhammad; Baehaqi, Ahmad; Kamal, Mustafa; Kian, Behnam (Journal of Islamic Economic Laws, 2025)
This study aims to test the effect of the characteristics of the Board of Directors and the Sharia Supervisory Board on the distribution of Zakat to third parties by Islamic banks in Indonesia. This research uses an associative quantitative approach using panel data regression. The data is secondary from Islamic banks' annual reports in Indonesia registered with OJK for 2021-2023. The sampling method used was purposive sampling, and a sample of 11 Islamic banks with 33 annual reports. The results showed that the number of meetings of the Board of Directors and the number of meetings of the Sharia Supervisory Board did not affect the distribution of Zakat. Meanwhile, the educational background of the Board of Directors has a negative effect on the distribution of Zakat, and the educational background of the Sharia Supervisory Board has a positive effect on the distribution of Zakat. The implications of this research can theoretically be used as a reference for further research. Practically, this research can be used as a reference material for Islamic banks in Indonesia and similar countries in optimizing social performance and evaluation material, especially for distributing Zakat to third parties.